A cutaneous malignant granular cell tumour: an uncommon entity with diagnostic challenge - Bala, Jyoti; Sharma, Ankur; Sharma, Sachin (International Journal of Research in Medical Sciences, 2023)
Granular cell tumour (GCT) is rare and accounts for approximately 0.5% of all soft tissue tumours. The malignant GCT (MGCT) especially cutaneous malignant granular cell tumour is extremely rare constituting 1-2% of all granular cell tumours and mostly found in the subcutaneous soft tissues of lower exrtremities, especially thighs. The uncommon occurrence of cutaneous MGCT and their histopathological similarities with other entities make diagnosis difficult in some cases. Here we report a case of 36 years old male patient who presented with a mass in the skin of right lower abdominal wall which has been increased gradually over the last one year without pain. The size of the mass is approximately 6.5 cm in greatest dimension, firm in consistency with surface irregularity and ulceration diagnosed as malignant GCT at the histopathological examination showing focal ulceration and lined by keratinized stratified squamous epithelium revealing acanthosis and pseudoepitheliomatous hyperplasia. The dermis show neoplastic epithelioid cells arranged in sheets and nests with vesicular chromatin, conspicuous to prominent nucleoli, and abundant amount of fine granular eosinophillic cytoplasm. Mitosis is more than 2/10HP. Immunohistochemical stains for S-100, CD 68 and vimentin were positive in the lesional cells.